Characteristics of demersal fish community structure during summer hypoxia in the Pearl River Estuary, China - Han Lai; Sheng Bi; Huadong Yi; Haiyang Li; Xuchong Wei; Gongpei Wang; Dingli Guo; Xuange Liu; Jiahui Chen; Qiuxian Chen; Zhilun Zhang; Shuang Liu; et al. (Ecology and Evolution, 2024)
Abstract In recent decades, hypoxic areas have rapidly expanded worldwide in estuaries and coastal zones. The Pearl River Estuary (PRE), one of China's largest estuaries, experiences frequent seasonal hypoxia due to intense human activities and eutrophication. However, the ecological effects of hypoxia in the PRE, particularly on fish communities, remain unclear. To explore these effects, we collected fish community and environmental data in July 2021 during the summer hypoxia development period. The results revealed that bottom‐layer dissolved oxygen (DO) in the PRE ranged from 0.08 to 5.71 mg/L, with extensive hypoxic zones (DO ≤ 2 mg/L) observed. Hypoxia has varied effects on fish community composition, distribution, species, and functional diversity in the PRE. A total of 104 fish species were collected in this study, with approximately 30 species (28.6%) exclusively found in hypoxic areas. Species responses to hypoxia varied: species such as Sardinella zunasi, Coilia mystus, and Nuchequula nuchalis were sensitive, while Decapterus maruadsi, Siganus fuscescens, and Lagocephalus spadiceus showed higher tolerance. Within the hypoxia area, dissolved oxygen was the main limiting factor for fish community diversity. Functional diversity (FDiv) decreased with higher dissolved oxygen levels, indicating a potential shift in the functional traits and ecological roles of fish species in response to changing oxygen conditions. Further analysis demonstrated that dissolved oxygen had a significantly stronger effect on fish community structure at hypoxic sites than in the whole PRE. Moreover, other environmental variables also had significant effects on the fish community structure and interacted with dissolved oxygen in the hypoxia area. These findings suggest that maintaining sufficient dissolved oxygen levels is essential for sustaining fish communities and ecosystem health in the PRE. This study provides novel insights into the effects of hypoxia on fish communities in estuarine ecosystems and has significant implications for the ecological health and management of the PRE.